Comparison of vacuum impregnation and soaking techniques for addition of the probiotic Lactobacillus acidophilus to minimally processed melon. (5th September 2017) - de Oliveira, Patrícia Martins; Ramos, Afonso Mota; Martins, Eliane Maurício Furtado; Vieira, Érica Nascif Rufino; Soares, Ariana de Souza; de Noronha, Marcel Cardoso
Summary: This study aimed to evaluate the vacuum impregnation (VI) and soaking methods in the addition of Lactobacillus acidophilus LA‐3 to minimally processed melon (MPM). The melons were washed, sanitised in chlorine solution (200 mg L −1 ), peeled and cutted into cubes. Lactobacillus acidophilus LA‐3 (1.4 × 10 10  CFU g −1 ) were added to the MPM through both techniques. The L. acidophilus LA‐3 count in MPM was similar to those commonly found in dairy products having probiotic claim, but VI was more efficient than soaking in maintaining the viability (8.61 and 7.98 Log CFU g −1, respectively). The pH, acidity and soluble solids were not affected by probiotic culture and the incorporation technique; however, the VI affected the firmness of fruit. The MPM was within Brazilian standards for their microbiological characteristics. MPM may be used as a carrier of probiotic bacteria, being one more alternative for individuals who consume probiotic products. Abstract : Comparison of vacuum impregnation and soaking techniques for addition of the probiotic Lactobacillus acidophilus to minimally processed melon.